Death on Bull Path - Doyle, Carrie, 1972- (Hamptons murder mysteries, 2021)
"After the craziness of August, the end of summer is supposed to bring peace and tranquility to the posh seaside enclave of East Hampton, New York. Antonia Bingham, chef and proprietor of the town's prestigious Windmill Inn, has been lining up and looking forward to trying some new recipes in the quiet, golden days of September. But when a Labor Day visit from two slick Wall Streeters ends with their gruesome deaths in a summer rental house, Antonia is quickly pulled back into the bedlam. With mysterious guests (and possible suspects) popping in and out of the inn, Antonia has no choice but to put on her sleuthing cap. The timing couldn't be worse, because Nick Darrow, Antonia's movie star crush, is back in town, available and ready for a commitment... and Antonia's sinister ex-husband might make an appearance, too. In Death on Bull Path, the fourth book of the bestselling cozy series, Antonia Bingham will take on everything the Hamptons can throw at her!"--